Using ARTEMIS pickup ion observations to place constraints on the lunar atmosphere. Issue 1 (31st January 2013) - Halekas, J. S.; Poppe, A. R.; Delory, G. T.; Sarantos, M.; McFadden, J. P.
Abstract : We present a method for deriving constraints on the structure and composition of the lunar atmosphere by using pickup ion measurements from ARTEMIS, mapping observed fluxes from the spacecraft location to derive production rates at the source region, and fitting to a parameterized neutral atmosphere model. We apply this technique to ~12 min of high‐resolution burst data collected by ARTEMIS P2 above the sunlit lunar surface, in the dawnside terrestrial magnetosheath. During this time period, ARTEMIS observed multiple velocity components, requiring the presence of multiple species and/or source regions. We use species at or near masses 12, 16, 24, 28, and 40 to derive a best‐fit model that proves consistent with most known abundances and limits on neutral densities as well as predictions thereof. However, we find indications of large neutral abundances at mass ~16, exceeding optical limits on oxygen by a factor of ~20, possibly indicating either "seeding" of the Moon by terrestrial oxygen during its magnetotail passage or significant contributions by OH or CH4 . We also derive new upper limits on the abundance of OH and Al in the atmosphere. Key points: We use pickup ion data from ARTEMIS to constrain the lunar atmosphere A mix of 12, 16, 24, 28, 40 fits data. We also obtain new upper limits on Al & OH Our model has large density at mass 16, suggesting excess O, or OH or CH4